A Retrospective Analysis of Mid-Term Paitent Follow-ups After Partial Atrioventricular Septal Defect Repair: A Unicenter Experience - Çağatay Bilen; Gökmen Akkaya; Osman Tuncer; Yüksel Atay (Galenos Publishing House, 2019)
INTRODUCTION: Partial atrioventircular septal defect is also known as ostium primum type atrial septal defect. Complications such as postoperative atrioventricular valve insufficiency, complet atrioventricular bundle blocks that requireing pace-maker and left ventricle outflow obstruction may occur in postoperative period. This study presents the surgical correction results of partial atrioventircular septal defect, thus we aimed to determine the comorbidities and mid-term outcomes. In this study, we aimed to report the results of partial atrioventircular septal defect. correction operations, comorbidities and mid-term data after discharge. METHODS: Overall 41 patients of who underwent surgical correction with the diagnosis of partial atrioventircular septal defect between 2005-2017 in our institute were included in this study. Hospital records were retrospectively analyzed. The patients were evaluated via transthoracic echocardiography in preoperatively and at first, third, sixth and twentieth months of postoperative period, afterwards, the examinations countinued by yearly interval. RESULTS: Only one hospital mortality occured due to congestif heart failure while there was no mortality in postoperative period. A permenant pace maker had to insert owing to total atrioventricular block development. After discharge, left atrioventricular valve insufficiency was observed as significantly improved. DISCUSSION AND CONCLUSION: As a consequence of paying maxiumum effort for to avoid bundle block development and to perform an adequate valve repair during surgical process, the reoperation requirements in long term follo-up may be considerably reduced in patients with partial atrioventircular septal defect.